2022
DOI: 10.3389/fpsyg.2022.1057475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute exercise intensity on cognitive inhibition and well-being: Role of lactate and BDNF polymorphism in the dose-response relationship

Abstract: IntroductionThere is evidence in the literature that acute exercise can modify cognitive function after the effort. However, there is still some controversy concerning the most effective exercise modality to improve cognitive function in acute interventions. Regarding these different exercise modalities, the dose–response relationship between exercise intensity and cognitive response is one of the most challenging questions in exercise and cognition research.MethodsIn this study, we tested the impact of modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Thus, HR exhibited only a marginal increase following EMS, whereas conventional EX, contingent on intensity, was documented to induce a significant elevation in HR [45]. In terms of BP, no significant change was observed during the EMS protocols, while it is established that EX elevates BP by up to 30% [44]. Furthermore, while conventional EX was reported to potentially decrease SaO 2 by over 5% [46], our study indicated that EMS resulted in a SaO 2 2% reduction of only 2%.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, HR exhibited only a marginal increase following EMS, whereas conventional EX, contingent on intensity, was documented to induce a significant elevation in HR [45]. In terms of BP, no significant change was observed during the EMS protocols, while it is established that EX elevates BP by up to 30% [44]. Furthermore, while conventional EX was reported to potentially decrease SaO 2 by over 5% [46], our study indicated that EMS resulted in a SaO 2 2% reduction of only 2%.…”
Section: Discussionmentioning
confidence: 87%
“…Compared to conventional EX, our results demonstrate that EMS only partially replicates the effect of EX. Indeed, a high-intensity EX protocol was reported to enhance the Stroop task in all conditions and to affect more mood aspects [44], as, in addition to anxiety that was reduced in our EMS experimental conditions, depression, confusion, and anger were also reduced after acute EX [2]. These discrepancies are most likely due to the difference in muscular mass involved when comparing EMS to conventional EX, as well as to the mechanisms triggered in response to these two different paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are important phargocytic cells normally elevated at early stage of stressed conditions [29]. Monocytes are known to be the largest type of leucocyte and can differentiate into macrophages and myeloid lineage dendritic cells, hence, they help in fighting bacteria, viruses, and other infections in the body, thereby influencing the process of adaptive immunity [30]. The platelets level is known to aggregate where there is wound healing or inflammation, from the results the groups treated with 200mg/kg of ginger Alligator pepper combinations suppressed the platelets aggregation while 100mg/kg of ginger and Alligator pepper enhanced platelets aggregation comparing it to the groups treated with the standard drug, thereby enhancing the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 10 studies conducted with adults reported that regardless of the exercise intensity, those who engaged in physical ac2vity experienced an improvement in emo2on regula2on skills compared to those who did not (Liu et al, 2022). Some suggest the intensity-response rela2onship follows an inverted U pakern, wherein exercise needs to surpass a certain intensity threshold to ac2vate the hypothalamus-pituitary-adrenal hormonal axis, but high intensity exercise can poten2ally over-ac2vate the stress system, triggering a surge in cor2sol that may heighten stress and anxiety (Ballester-Ferrer et al, 2022;Chan et al, 2019). These findings are par2ally corroborated by early childhood research showing that children engaging in a moderate amount of physical ac2vity demonstrated the highest inhibitory control in a task-based assessment, while those who involved in lower or very high ac2vity levels showed lower subsequent levels of execu2ve func2ons (Koepp et al, 2022).…”
Section: Intensity and Dura/ons Effectsmentioning
confidence: 99%
“…Interval training involves individuals engaging in brief, intense exercise sessions, follow by periods of rest and recovery to prevent over-ac2va2on of the stress system. Interval training has been shown to induce greater expression of neurotrophic factors, such as brain-derived neurotrophic factor, that play a central role in cogni2ve func2oning and brain plas2city (Ballester-Ferrer et al, 2022;Winter et al, 2007). As interval training may not be appropriate during early-childhood, further research is required to determine how the same physiological response can be achieved in a developmentally appropriate way for young children.…”
Section: Intensity and Dura/ons Effectsmentioning
confidence: 99%